War in Marxian and Engelsian Thought: The Crimean War (1853-56) and the “Sixth Power in Europe” - Papadopoulos, Nikos (Public Realm. Postgraduate and Early Career Journal of Political Philosophy, 2025)
The Crimean War (1853-56) attracted Karl Marx and Friedrich Engels’ political interest. The two thinkers came up with a long volume of articles and letters they wrote as dispatches for the American newspaper The New York Tribune. I tap into the said corpus to glean past perspectives on a modern war as a major geopolitical phenomenon involving three Great Powers —namely England, France and Russia— and the crumbling Ottoman Empire, and directly impinging upon the post-Vienna Congress established European socio-political order. I argue, based on Marx and Engels’ commentaries, that in the Marxian philosophical constellation, war is conceptualised and projected as a harbinger of a pan-European proletarian revolution. As a “sixth power in Europe” that could hold sway over —foremost by precipitating— the course of events which would usher in a radical social transformation. Besides, the under-theorisation of modern war in the Marxian and Marxist intellectual traditions, the reasons behind it, and Étienne Balibar’s distinct theoretical approach to the coupling of war and revolution are also presented and discussed.